Kinetics of the thermal and photochemical decomposition of aquapentacyanoferrate(III) in aqueous solution - Ronco, Silvia Elisa (1987)
The kinetics of the thermal and photochemical decomposition of aquapentacyanoferrate(III) ion in aqueous solution in the presence ofo-phenanthroline was studied spectrophotometrically. The first-order rate constant (k; ϑ) at 30° C [I=1 M(NaCl)] for the thermal reaction is (1.49±0.13)×10−6 s−1 with ΔH; ≠=(158±7)kJ mol−1 and ΔS≠=(42±4) JK−1 mol−1. The initial quantum yield for the photochemical reaction at pH=7 is independent of the light intensity and is (1.49±0.33)×10−2 mol einstein−1.